Sosialisasi Dan Pendampingan Terkait Opsen PKB Dan BBNKB Di Kabupaten Paser - Abadan Syakura, Muhammad; Juri, Mat (CV. Multi Kreasi Media, 2025)
The implementation of the surcharge (opsen) on Motor Vehicle Tax (PKB) and Motor Vehicle Title Transfer Fee (BBNKB), as regulated by Law Number 1 of 2022 on Fiscal Relations between Central and Regional Governments, has created an urgent need to improve public tax literacy, particularly at the village level. Changes in the structure of motor vehicle taxation may lead to confusion, misunderstanding, and public resistance if not accompanied by adequate socialization. This community service program aims to enhance public understanding of the concept, legal basis, and mechanism of PKB and BBNKB surcharges, while fostering positive attitudes toward regional tax compliance. The activity was conducted in Tanah Grogot and Muara Samu Sub-districts, Paser Regency, using an educative and participatory approach through material presentations, interactive discussions, tax calculation simulations, and consultative assistance addressing real issues faced by the community. The implementation method involved collaboration among lecturers, students, and the Regional Revenue Agency (Bapenda) of Paser Regency as the main partner. The results indicate an improvement in participants’ understanding of PKB, BBNKB, and surcharge structures, increased ability to critically interpret tax billing components, and a more positive attitude toward motor vehicle tax obligations. Moreover, the program facilitated constructive dialogue between the community and local government in resolving administrative tax issues. Overall, this community service contributes to strengthening tax literacy and supporting the sustainable optimization of regional tax revenues.